The Relationship Between Total Quality Management Practices and Secondary School Performance with Mediating Effect of Organizational Culture in Abu Dhabi: A Structural Equation Modeling Approach - Alhosani, Khaled Sultan; Yaakub, Kamarul Bahari (European Journal of Multidisciplinary Studies, 2021)
This study aims to investigate the structural equation modeling to determine the relationship between total quality management practices and secondary school performance with mediating effect of organizational Culture in Abu Dhabi. Quantitative research design was adopted to obtained information from respondents. A total of 320 employees of school were selected as a sample through the stratified and quota random sampling technique. Data analysis using structural equation modelling was used. The results of the study indicated that significant relationship was found between total quality management practices and secondary school performance with value of -.01. The findings showed that significant relationship exist between total quality management practices and organizational culture with value of .86; significant relationship was also found between organizational culture and secondary school performance .87. Further, the findings reported that organizational culture showed complete mediation between total quality management practices and secondary school performance. This study believed that total quality management would yield good results if secondary school in Abu Dhabi make use of it to improve school performance.